Clinical value of controlling nutritional status scores in patients with hepatocellular carcinoma - Rongqiang Liu; Lei Ji; Chenxuan Zhang; Jing Ye; Xinyi Li; Wangbin Ma; Jia Yu; Weixing Wang (Frontiers in Nutrition, 2025)
BackgroundNumerous studies have highlighted the significance of controlling nutritional status (CONUT) score in the prognosis of patients with hepatocellular carcinoma (HCC). However, the precise role of the CONUT scor in predicting HCC prognosis remains unclear. This study aimed to investigate the prognostic significance of the CONUT scores in patients with HCC through an updated meta-analysis.MethodsThree internationally recognized authoritative databases (PubMed, Web of Science and Embase) were searched. The research focused on the relationship between CONUT score and prognosis in patients with HCC. The deadline for literature search was October 23, 2024. In this study, hazard ratios (HRs) and odds ratios (ORs) were used as the primary statistical indicators for pooled analysis. All calculated HRs and ORs were accompanied by 95% confidence intervals (95% CIs). Data analyses were performed using STATA software, version 12.0.ResultsA total of 19 relevant studies encompassing 7,963 patients were included in this meta-analysis. The CONUT score was significantly associated with unfavorable survival outcomes, including overall survival (OS) (HR: 1.58, 95% CI: 1.33–1.87), disease-free survival (DFS) (HR: 2.06, 95% CI: 1.34–3.18), recurrence-free survival (RFS) (HR: 1.48, 95% CI: 1.09–2.00), and progression-free survival (PFS) (HR: 1.93, 95% CI: 1.24–2.99). Subgroup analysis further confirmed the prognostic value of the CONUT score. Moreover, high CONUT score was strongly associated with tumor differentiation (poor vs. moderate/well) (OR: 1.32, 95% CI: 1.16–2.35) and tumor number (solitary vs. multiple) (OR: 1.25, 95% CI: 1.19–1.84).ConclusionHCC patients with high CONUT scores usually face a worse survival prognosis. The CONUT score may be a valid prognostic indicator for patients with HCC.